Valdemiro Santiago parte para o abraço: Estratégias midiáticas e interacionais envolvidas na mundial igreja do poder de deus - Bandeira, Alexandre Dresch (Universidade do Vale do Rio dos Sinos, 2017)
In an increasingly mediatized society, new churches arise with countless denominations using the media space to send their messages, thus becoming part of a new social context that is more and more disputed within communication means. Some of these churches already have an evolved expertise, ranging from the religious to the media realm, who have dominated their grammars and stand out from the others in relation to the current media. This case study on the World Church of God's Power and its founder, Apostle Valdemiro Santiago, aimed at investigating the media and interactional strategies used by Valdemiro Santiago in the worship service of his church, and if these strategies classify the it as a media church, or as a church that uses these means to get its message across. During the journey, we verified all the media and communication strategies that have been applied by Santiago, making him unique in regards to his communication with his people. To answer these issues, Peirce's abductive investigative method was used, which is a theory that can be related to the object of study. In the course of the research, we were surprised by several situations that helped us understand how this very peculiar way of making religion arises. In an environment where there is no place for amateurism, we have seen that the World Church differentiates itself through the performance of its founder and that the current moment of mediatization of society allows its proposals and movements to transform the World Church in the second largest Brazilian neo-Pentecostal Church, and Santiago in the second richest preacher in Brazil. A world of possibilities emerges, in which individualism is favorable for this type of proposal, and in which religion becomes a private enterprise, discourse and property of a single person, and where, due to the insertion in the practices of the media, enables a swift transition through them more naturally in both fields. We concluded, then, that Santiago embraces these possibilities and inaugurates a new way of doing television and religion.
Keywords: Mundial Igreja do Poder de Deus; Valdemiro Santiago; Mídia; Religião; Midiatização; World Church of God’s Power; Media; Religion; Mediatization; ACCNPQ::Ciências Sociais Aplicadas::Comunicação